A service evaluation of parent adherence with dysphagia management therapy guidelines: reports from family carers supporting children with complex needs in Greece. Issue 3 (30th January 2020) - Charpentier, Alexia; Morgan, Sally; Harding, Celia
Abstract: Purpose: Many children with complex needs exhibit eating, drinking, and/or swallowing disorders (dysphagia). These children often have associated learning needs, and require assistance from carers for daily tasks such as eating and drinking. The aim of this study was to identify which strategies to manage dysphagia were challenging for family carers, and reasons for any non-adherence. Method: In this service evaluation researchers observed carers during mealtimes, and investigated carer opinions of strategies used to minimise the risks of dysphagia. Eight children with complex needs aged 3.4–7.5 years and their primary family caregiver participated. Results: Adherence with speech and language pathologists' dysphagia recommendations overall was over 50% in all but one case. For specific strategies, the highest adherence was observed for diet modifications of foods (89%), communication during the mealtime (83%), amount of food to present (81%), and the pacing of fluids and foods (81%). Lower levels of adherence were identified in relation to postural management (58%), environmental changes (58%), utensils (56%), and preparatory strategies (49%). Conclusions: Adherence with use of strategies to support mealtimes was over 50% in all but one case. Findings suggest that support is essential to promote safe mealtimes, reduce family carers' stress and increase knowledge, confidence, and adherence in implementing dysphagia guidelines in the family home. Implications for rehabilitation: Difficulties with eating, drinking and swallowing (dysphagia) can impact on the parent–child mealtime experience. Mealtime strategies as recommended by a speech-language pathologist can support children who have difficulties eating, drinking, and swallowing. Some strategies to support eating, drinking, and swallowing are easier for carers to adhere to than others.